2005
DOI: 10.1097/01.paf.0000154255.67466.8e
|View full text |Cite
|
Sign up to set email alerts
|

Ancillary Studies in Amniotic Fluid Embolism

Abstract: The incidence of amniotic fluid embolism during pregnancy is approximately 1/50,000 and has a mortality rate in excess of 80%. The postmortem diagnosis of amniotic fluid embolism can be challenging for forensic investigators and pathologists. At autopsy, usually signs of disseminated intravascular coagulation suggest an amniotic fluid embolism. A definitive diagnosis of amniotic fluid embolism cannot be made until ancillary studies are performed on the decedent's tissues. We report a case of a 37-year-old G3P2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…2,78 These constituents can be specifically identified by using immunohistochemical markers for cytokeratin AE1/AE3, Alcian blue or mucicarmine staining, oil red O staining, and polarized light, respectively. 8183 Kobayashi et al, 84 reported that immunohistochemical staining using monoclonal antibody TKH-2 is a more sensitive method to detect meconium and amniotic fluid-derived mucin in the lung sections of patients with AFE than conventional hematoxylin eosin or Alcian blue staining. Oi et al 85 reported positive TKH-2 staining within the pulmonary vasculature in 14 of 15 (93%) women with AFE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,78 These constituents can be specifically identified by using immunohistochemical markers for cytokeratin AE1/AE3, Alcian blue or mucicarmine staining, oil red O staining, and polarized light, respectively. 8183 Kobayashi et al, 84 reported that immunohistochemical staining using monoclonal antibody TKH-2 is a more sensitive method to detect meconium and amniotic fluid-derived mucin in the lung sections of patients with AFE than conventional hematoxylin eosin or Alcian blue staining. Oi et al 85 reported positive TKH-2 staining within the pulmonary vasculature in 14 of 15 (93%) women with AFE.…”
Section: Resultsmentioning
confidence: 99%
“…Increased serum levels of tryptase, a marker of mast cell degranulation, in women with AFE have been reported by some authors 123,124 but not by others. 83,125 Benson et al 57 reported that serum tryptase was negative in all of the 6 women with AFE. However, they found that decreased serum levels of C3 and C4 complement had sensitivities between 88–100% and a specificity of 100% for the diagnosis of AFE.…”
Section: Diagnosismentioning
confidence: 99%
“…3,10,12,13 Increased tryptase levels have been used to attempt AFE diagnosis, with the theory that AFE may be equated to anaphylaxis. PAF is thought to cause increased vascular permeability; bronchoconstriction; platelet aggregation; recruitment of leukotrienes, cytokines, and thromboxanes; and a prostaglandin cascade.…”
Section: Etiologymentioning
confidence: 99%